PENGEMBANGAN DESAIN KAIN JUMPUTAN PALEMBANG UNTUK MENINGKATKAN INDUSTRI KREATIF - Rusdianasari Rusdianasari; Ibnu Hajar; Indri Ariyanti; Yohandri Bow (Aptekmas Jurnal Pengabdian pada Masyarakat, 2020)
The development of micro, small and medium enterprises (MSMEs) is the basis of the economy in improving the national economic rate because most of the existing businesses in Indonesia are small and medium enterprises. Among those small and middle enterprises, Palembang Jumputan Textile has its own characteristics in patterns and colors. Under the influence of a certain pattern, Jumputan Textile has been known and spread in Sumatra and even in Indonesia and overseas. Nowadays, the regional pattern in every province has been in the fast track of development nationally. The creative industry in Palembang is including around 300 industries of Songket and Jumputan Textile recorded in this city. Community service activities have been conducted to two small and medium enterprises in the center of Palembang Jumputan Textile. The community activities are including the development of pattern making or motif on fabric, dyeing process, and online marketing technique in attempt to improve the sales.